Investigation of the effect of dye sensitized solar cell efficiency of donor and anchor groups in phthalocyanine compounds - Karadogan, Betul; Erden, Ibrahim (IOS PRESS, 2023)
In order to obtain higher power conversion performance in dye-sensitized solar cells, phthalocyanine compounds (ZnPc-1 and ZnPc-2) containing electron donor methoxy groups and aldehyde groups as anchors were synthesized in this study. The photovoltaic and electrochemical properties of these compounds were studied and their applicability as photosensitizers in DSSCs was investigated. The photovoltaic cell efficiencies (PCE) of the devices were in the range of 0.43-0.76 % under simulatedAM1.5 solar irradiation of 100 mW/cm(2). Considering the photovoltaic performance of the produced DSSC devices, the anchor group and the chelate effect, it was observed that the efficiency increased, respectively, ZnPc-1 < ZnPc-2. The highest PCE value of 0.76 % was obtained with asymmetric ZnPc-2 based DSSC under. It has been explained that methoxy groups are electron donors and contribute to intramolecular electron mobility and that better electron transfer with single aldehyde anchor increases cell efficiency. In addition, the increase in the number of methoxy groups with known donor properties on the molecule also contributed to the increase in cell efficiency by increasing electron transfer. All compounds synthesized were characterized using FTIR, UV-vis and MS spectroscopic data.
Keywords: Phthalocyanine; dye-sensitized solar cells; methoxy groups; D-pi-A dyes; D-PI-A; DESIGN; Chemistry